(untitled) (Research, Society and Development, 2020)
Sex workers have experiences that raise questions about what can satisfy them sexually and, thus, have a good quality of life. The objective was to analyze the representations meanings of sex workers about sexual satisfaction in their daily lives. Qualitative study, based on the Theory of Social Representations, carried out in the municipality where the Alto Sertão Productive Region of Bahia (Brazil) is located, in areas of social vulnerability, where the places of prostitution are located. 132 women participated in the study. The Free Word Association Technique was used for data collection, with the inductive term “sexual pleasure/satisfaction”. The corpus was organized and processed using the IRAMUTEQ software that issued the Factorial Correspondence Plan, Maximum Similitude Tree and the Word Cloud. The results from the three forms of analysis demonstrated homogeneity in social representations, as the group’s unconscious presented the term “money” as the central and main representational field about “sexual satisfaction”, evading the idea that sex workers feel orgasm in the sexual act with clients. Thus, reflecting on the “sexual satisfaction ’, anchored in the Theory of Social Representations, will enable health professionals to rethink their practices, considering the specificities of this population segment, with regard to the planning of sexual health care of women who work sexual, focused on libido and the subjective part of sexuality, extrapolating the common sense that the focus of health care for prostitutes should be focused only on preventing sexually transmitted infections.